Physicochemical, potential nutritional, antioxidant and health properties of sesame seed oil: a review - Oboulbiga, Edwige Bahanla; Douamba, Zoénabo; Compaoré-Sérémé, Diarra; Semporé, Judith Nomwendé; Dabo, Rasmata; Semde, Zénabou; Tapsoba, Fidèle Wend-Bénédo; Hama-Ba, Fatoumata; Songré-Ouattara, Laurencia T.; Parkouda, Charles; Dicko, Mamoudou H. (Frontiers in Nutrition, 2023)
Sesame (Sesanum indicum L.) is one of the primary annual oilseeds grown in Africa and Asia. Sesame seed oil (SSO) is of great economic and human nutrition interest worldwide. Due to its composition in phytochemical antioxidants and profile in unsaturated fatty acids, sesame is used as a biological source of essential fatty acids. It contains bioactive compounds such as lignans (sesamin, sesamol, sesamolin), tocopherols and phytosterols. The oleic/linoleic fatty acids ratio of sesame makes it important for human health. SSO has bioactive compounds that can help prevent certain cardiovascular, metabolized and coronary diseases. The ω-3 and ω-6 fatty acids in SSO are precursors to eicosanoids that regulate the immune system and inflammatory functions. The essential fatty acids contained in this oil are essential for cell construction and highly recommended during the first trimester of pregnancy. The consumption of SSO allows both a decrease in the LDL-cholesterol complex and an increase in the HDL-cholesterol complex. It regulates blood sugar and may have favorable effects on people with liver cancer and those developing fatty liver disease. In this review, the nutritional value, antioxidant properties, and health benefits of SSO have been compiled to provide collective information of nutritional and medical interest.